(untitled) (Desarrollo Económico. Revista de Ciencias Sociales, 2022)
This paper measures the wealth and potential income generation of unconventional fuels from Vaca Muerta shale formation in Argentina, the second unconventional gas and the fourth unconventional oil reservoir in the world, according to standard investment valuation methodology. This Valuation methodology takes into account several income projections, investment and operational costs, learning curves, initial productivity and expected performance of wells, spot and forward prices, and latest regulatory framework in Argentina. Potential revenues and investments would not make Argentina a hydrocarbon world power as Saudi Arabia. Vaca Muerta shale play’s potential income would not allow Argentine society to be “saved” defined as boosting consumption effortlessly just because of Vaca Muerta’s wealth. Its potential output would not generate enough foreign exchange to the point of being an alternative to agricultural exports (including exports of manufacturing agro based products), and hence, becoming a tool to fix the country’s chronic external gap. Moreover, the magnitude of potential revenue (with extreme hypothesis of null internal gas consumption and total replacement by unconventional gas) would amount to only 50% of the traditional Argentinean exports. High probability benchmarking scenario shows that Vaca Muerta wealth value (net present value, npv) is nearly 7% of Argentinean gross domestic product (gdp). Calibration of more extreme lower probability scenarios, suggests that net present value could reach not more than 30% of gdp. Our findings contrast with a popular call from politicians that value the formation by a multiple equivalent to 10 times Argentina´s gdp, without taking into account the economic and commercial feasibility of expected income and costs by traditional definitions of reserves. However, Vaca Muerta is an investment opportunity that could impact on Argentinean hydrocarbons market and the economy of Neuquén province, contributing to the necessary transition towards a more renewable-centric energy matrix. Special products such as unconventional oil and gas, soybeans as well as other natural resource-based goods could trigger investment opportunities, but would not enable Argentine society as a whole to to live of rents”. To achieve the desired objective of economic and social development, Argentina needs to sustain economic growth in a stable macroeconomic framework, taking advantage from its human and natural resource endowment by increasing domestic savings, investment and productivity.